Bedarfsorientiertes Kapazitätsmanagement in Supply Chains - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Internationale Standortwahl als strategisches Logistikproblem - Betz, Stefan (Ausgewählte Probleme des Logistikmanagements)

Dual-path source engineering in integrated quantum optics - Kruse, Regina; Sansoni, Linda; Brauner, Sebastian; Ricken, Raimund; Hamilton, Craig S.; Jex, Igor; Silberhorn, Christine (Physical Review A)

Programs from Proofs of Predicated Dataflow Analyses - Jakobs, Marie-Christine; Wehrheim, Heike (Proceedings of the 30th Annual ACM Symposium on Applied Computing)
Programs from Proofs" is a generic method which generates new programs out of correctness proofs of given programs. The technique ensures that the new and given program are behaviorally equivalent and that the new program is easily verifiable, thus serving as an alternative to proof-carrying code concepts. So far, this generic method has one instantiation that verifies type-state properties of programs. In this paper, we present a whole range of new instantiations, all based on data ow analyses. More precisely, we show how an imprecise but fast data ow analysis can be enhanced with a predicate analysis as to yield a precise but expensive analysis. Out of the safety proofs of this analysis, we generate new programs, again behaviorally equivalent to the given ones, which are easily verifiable" in the sense that now the data ow analysis alone can yield precise results. An experimental evaluation practically supports our claim of easy verification.

20 Jahre Lernen mit dem World Wide Web - Technik und Bildung im Dialog - Keil, Reinhard; Harald, Selke

Systematik zur Entwicklung einer produktlebenszyklusorientierten Geschäftsmodell-Roadmap - Peitz, Christoph

Systematik zur frühzeitigen Absicherung der Sicherheit und Zuverlässigkeit fortschrittlicher mechatronischer Systeme - Dorociak, Rafal

Augmented & Virtual Reality in der Produktentstehung: Grundlagen, Methoden und Werkzeuge; Interaktions- und Visualisierungstechniken, Virtual Prototyping intelligenter technischer Systeme mit AR/VR - Gausemeier, Jürgen; Grafe, Michael; Meyer auf der Heide, Friedhelm

Systematik zur wirtschaftlichkeitsorientierten Konzipierung Intelligenter Technischer Systeme - Vaßholz, Mareen

Verification and Simulation of Self-Adaptive Mechatronic Systems - Heinzemann, Christian